HUBUNGAN KEPEMIMPINAN GURU DAN IKLIM ORGANISASI KELAS DENGAN POLA PERILAKU BELAJAR SISWA SMP NEGERI 1 BUMI AGUNG KABUPATEN LAMPUNG TIMUR - Kurniawati, Endah (UNIVERSITAS MUHAMMADIYAH METRO, 2016)
The efforts of effective leadership is needed to drive, move, and control the execution of the tasks of the organization in classroom so that the learning process can be carried out effectively and targeted to the achievement of established goals. This research aimed in revealing: (1) the Teachers Leadership corelates to the Studentsâ Learning Style; (2) the Organizational Climate of Classroom corelates to the Studentsâ Learning Style; (3) the Teachers Leadership and Organizational Climate of Classroom corelates to the Studentsâ Learning Style. The population in this research were all teachers and students. The sample technique was total sampling, so all of the members of population were the samples of the research. Data were collected by using a set of questionnaires and test. The first and second hyphotesis were analyzed by means of the simple correlation and regression techniques, and the third hyphothesis were analized by the multiple correlation and regression technique.The findings of research reveal that: (1) the Teachers Leadership contributes significantly towards the the Studentsâ Learning Style; (2) the Organizational Climate of Classroom contributes significantly towards the Studentsâ Learning Style; (3) the Teachers Leadership andÂ the Organizational Climate of Classroom togather contributes significantly towards the the Studentsâ Learning Style. So it can be concluded thatÂ the Teachers Leadership and the Organizational Climate of Classroom are two important factorsÂ in contributing the Studentsâ Learning Style. The advantages of this research is to giveÂ ideas for school and teachers about the importance of teachers leadership and organizational climate of classroom for increasing positive studentsâ learning style, so teachers always increase their leadership of learning by learning and following workshops.